Design and bandwidth enhancement of zeroth-order resonator antenna using metamaterial - Sadiq Ahmed; Zaid A. Abdul Hassain; Hussein Ali Abdulnabi; Mohammed Al-Saadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In this paper, a compact configuration of zeroth-order resonator antenna is described. The unit cell zeroth-order resonator properties are introduced by composite right/left-handed transmission line approach is fed by coplanar waveguide. The proposed resonator is analyzed by changing the coupling space and stub length of the unit cell. The size of implemented resonator is (0.185 λ0 × 0.185 λ0 × 0.027 λ0) at the centre frequency. In this work, a zeroth-order resonator antenna design with enhanced bandwidth has been presented, and the size reduction by using the metamaterial inclusion. The proposed zeroth-order resonant antenna (ZORA) achieves a 64% reduction compared to a traditional λ/2 microstrip patch antenna. The bandwidth for the 10 dB return loss is 5.66 GHz (2.76 GHz to 8.42 GHz), the peak value of gain is 0.8 dBi and radiation efficiency of the designed antenna is 87% at 5.5 GHz. The return loss is about -59.48 dB at the center frequency. The competition among the simulated performances and other antennas shows that the proposed resonator achieves wide bandwidth. The performance of zeroth-order resonator antenna is evaluated by full-wave electromagnetic (EM) simulator HFSS11